DESCRIPCIÓN DEL DESARROLLO DEL PRÓTALO Y DEL ESPORÓFITO JOVEN DE PTERIS QUADRIAURITA RETZ. (PTERIDACEAE-POLYPODIIDAE). (POLIBOTÁNICA, 2019)
We describe gametophyte  morphology and young sporophyte of Pteris quadriaurita Retz. Studied material was collected in a cloud forest in Tototla, Xochicoatlán municipality, State of Hidalgo, México. The spores were sown in glass vessel of 125 ml prepared in the following manner: the glasses were layered with ceramic, river stone, mosquito net and three natural substrates (plant litter, maquique and moss) all previously sterilized and enclosed in plastic bag tied with copper wire. The cycle proved to be isosporeus with prothallial development corresponding to the Ceratopteris type. The gametophytes were only male, only female and few hermaphrodite. Young sporophytes were apogamous obtained around 231 days after sowing in moss and maquique, in plant litter, they were nor development.